Multifunctional electrolyte and lithium ion battery
The multi-functional electrolyte solution addresses the instability and safety issues of lithium-ion batteries by using specific additives to stabilize the silicon anode interface and form a protective layer, enhancing cycle performance and thermal stability.
Patent Information
- Application Number
- CN202411920139.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-24
AI Technical Summary
Current lithium-ion batteries with graphite anodes face challenges such as volume expansion, active particle breakdown, and instability of the solid electrolyte interface (SEI) during cycling, leading to reduced performance and safety concerns, especially at high temperatures, due to the limitations of graphite-based materials in meeting high energy density demands.
A multi-functional electrolyte solution is developed, comprising specific additives like 3-(4,4,5,5-tetramethyl-1,3,2-dioxaborinan-2-yl)-1-methylthio-1H-pyrazolo[3,4-b]pyridine and a second additive with a phosphorus-containing structure, which form a protective CEI membrane and enhance SEI stability, ion conductivity, and thermal stability, thereby improving the performance and safety of silicon-based anodes.
The electrolyte solution stabilizes the silicon anode interface, prevents volume expansion, and forms a protective layer that inhibits electrolyte decomposition and metal ion release, resulting in improved cycle performance, thermal stability, and safety of lithium-ion batteries, especially under high-temperature conditions.
Smart Images

Figure CN119725754A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium batteries, and in particular to a multifunctional electrolyte and a lithium-ion battery. Background Art
[0002] Lithium-ion batteries have become the first choice for the automotive industry to produce pure electric vehicles due to their high energy density, low self-discharge, long life, environmental protection, and reasonable cost. However, the current negative electrode materials mainly based on graphite are no longer sufficient to meet the market demand for high specific capacity of lithium batteries.
[0003] Anode materials with high specific capacity are an important breakthrough in improving the energy density of lithium-ion batteries. Silicon-based materials are considered to be the most likely anode materials to replace graphite because of their high theoretical specific capacity, suitable discharge potential and relatively abundant reserves in nature. However, there are many problems in the commercial application of single silicon in lithium-ion batteries. First, silicon-based materials as anodes will have volume expansion problems during battery cycles, and may cause the rupture of active particles, pulverization of pole pieces and the shedding of active materials. Secondly, the silicon anode is accompanied by a large volume expansion during the first cycle, which leads to the formation of solid electrolyte interface film (SEI) and consumption of lithium ions, reducing the first coulomb efficiency. During the cycle, due to the volume change of the electrode material, the SEI film at the silicon anode interface repeatedly grows and breaks, greatly affecting the cycle stability. More seriously, under high temperature conditions, severe side reactions and interface instability will accelerate the degradation of lithium-ion batteries. At the same time, high temperature conditions will also increase the risk of thermal runaway of the battery, causing battery safety issues. Summary of the invention
[0004] In order to solve the problems in the prior art, the present application provides a multifunctional electrolyte and a lithium-ion battery.
[0005] In a first aspect, the present application provides a multifunctional electrolyte, which adopts the following technical solution:
[0006] A multifunctional electrolyte comprises a first additive and a second additive, wherein the first additive comprises 3-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-1-toluenesulfonyl-1H-pyrrolo[2,3-b]pyridine-5-carbonitrile; and the chemical structure of the second additive is shown in Formula I:
[0007]
[0008] Among them, R 1 , R 2 , R 3 Each independently selected from -CH 2 CF 3 , -CHCF 3CF 3 、-CH 2 CF 2 CHF 2 Any one of .
[0009] The present application uses a first additive and a second additive in combination. The N atom on the cyano group in the first additive has a lone pair of electrons and can cooperate with the dioxaborolane group to complex the HF in the electrolyte and the hydrogen atoms in the water molecules, thereby playing a role in removing water and inhibiting acid, so as to improve the stability of the electrolyte and the stability of the silicon-containing negative electrode in the electrolyte, thereby improving the stability of the negative electrode interface, and avoiding the decrease in the cycle performance of the lithium battery caused by the expansion of the silicon negative electrode; at the same time, the second additive contains trivalent phosphorus, which will be preferentially oxidized compared to the first additive, and the trivalent phosphorus removes the oxygen generated on the positive electrode interface, oxidizes and decomposes to generate a protective layer containing alkyl phosphorus, thereby forming a protective CEI film on the electrode interface, which can effectively inhibit the decomposition of the electrolyte and the dissolution of transition metal ions at the positive electrode, avoiding the negative impact of the dissolution of transition metal ions on the stability of the SEI film, thereby further improving the stability of the SEI film at the negative electrode and improving the thermal stability of the electrolyte, which are all helpful to further improve the cycle performance of the silicon-containing negative electrode.
[0010] Furthermore, the second additive is combined with the first additive, and the combination of the sulfonyl group in the first additive and the fluorine element in the second additive can significantly improve the flame retardant effect of the electrolyte, thereby improving the fast charging safety of the lithium battery; at the same time, the pyridine group in the first additive is combined with the fluorine element in the second additive, which can not only improve the ionic conductivity of the electrolyte, but also form LiF with high ionic conductivity, which is helpful to improve the cycle performance and rate performance of the lithium battery.
[0011] Preferably, the second additive includes tris(1,1,1,3,3,3-hexafluoro-2-propyl)phosphorous acid.
[0012] Among them, the structural formula of N,O-bis(trimethylsilyl)trifluoroacetamide is The CAS number is 1434747-57-5; the structural formula of tris(1,1,1,3,3,3-hexafluoro-2-propyl)phosphorous acid is The CAS number is 66470-81-3.
[0013] Preferably, the mass proportion of the first additive in the electrolyte is 0.5%-2%.
[0014] Preferably, the mass proportion of the second additive in the electrolyte is 0.5%-1.5%.
[0015] By controlling the proportion of the first additive and the second additive in the electrolyte, on the one hand, while improving the stability of the electrolyte, a stable electrolyte environment can be provided for the film formation of the second additive at the positive electrode; on the other hand, it helps the coordination of the two, while improving the stability of the positive electrode interface film and the negative electrode interface film, and exerting the coordination effect of the sulfonyl group, pyridine group and fluorine element in the additive, which can not only improve the flame retardant properties of the electrolyte, but also help to further improve the cycle performance of the lithium battery.
[0016] Preferably, it also includes an organic solvent, a lithium salt and a lithium salt additive.
[0017] Preferably, the lithium salt additive includes at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide and lithium tetrafluoroborate.
[0018] Preferably, the lithium salt additive accounts for 0.2%-3% by mass in the electrolyte.
[0019] The present application helps to further improve the high temperature stability and rate performance of the electrolyte by adding a lithium salt additive to the electrolyte.
[0020] Preferably, the lithium salt comprises lithium hexafluorophosphate; and the concentration of the lithium salt is 1-1.5 mol / L.
[0021] Using LiTFSI and LiPF 6 Batteries with mixed electrolytes exhibit higher capacity retention, especially under high temperature conditions, and this mixed electrolyte can provide better rate performance.
[0022] Preferably, the organic solvent includes at least one of a linear carbonate and a cyclic carbonate.
[0023] Preferably, the linear carbonate includes at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and methyl propyl carbonate; the cyclic carbonate includes at least one of ethylene carbonate, fluoroethylene carbonate and propylene carbonate.
[0024] Preferably, the mass ratio of the linear carbonate to the cyclic carbonate is 60-80:20-40.
[0025] By using linear carbonates and cyclic carbonates as solvents, it is helpful to adjust the electrolyte to a suitable viscosity, thereby generating a stable SEI film on the surface of the negative electrode active material, and can improve the ionic conductivity and chemical stability of the electrolyte, thereby helping the first additive and the second additive to play a long-term cooperative role in the electrolyte, and further helping to improve the cycle performance, flame retardant performance and rate performance of the lithium battery.
[0026] In a second aspect, the present application provides a lithium-ion battery, which adopts the following technical solution:
[0027] A lithium ion battery comprises a positive electrode sheet, a separator, a negative electrode sheet and the multifunctional electrolyte as described above. DETAILED DESCRIPTION
[0028] For better understanding and implementation, the technical solution of the present application will be clearly and completely described below in conjunction with embodiments. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments.
[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0030] Unless otherwise indicated, all numerical values expressing quantities of ingredients, reaction conditions, and so forth used in the specification and claims are to be understood as modified by the term “about.” Accordingly, unless indicated to the contrary, the numerical parameters set forth herein are approximations that can vary depending upon the desired properties desired to be obtained.
[0031] As used herein, "and / or" means one or all of the mentioned elements.
[0032] As used herein, “including” and “comprising” encompasses the case where only the stated elements are present as well as the case where there are other elements other than the stated elements.
[0033] All percentages in this application are by weight unless otherwise stated.
[0034] Unless otherwise indicated, "a", "an", "an" and "the" used in this specification are intended to include "at least one" or "one or more". For example, "a component" means one or more components, so more than one component may be considered and may be employed or used in the implementation of the embodiment.
[0035] Example 1
[0036] 1. Preparation of Electrolyte
[0037] The mass proportion of the first additive in the electrolyte is 1.2%, the mass proportion of the second additive is 1%, the mass proportion of the linear carbonate and the cyclic carbonate in the organic solvent is 70:30, and the lithium salt concentration is 1.3 mol / L.
[0038] The first additive is 3-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-1-toluenesulfonyl-1H-pyrrolo[2,3-b]pyridine-5-carbonitrile, and the second additive is tri(1,1,1,3,3,3-hexafluoro-2-propyl)phosphorous acid, whose structural formula is The CAS number is 66470-81-3;
[0039] The lithium salt is lithium hexafluorophosphate;
[0040] The linear carbonates are diethyl carbonate DEC and ethyl methyl carbonate EMC, and the cyclic carbonates are fluoroethylene carbonate FEC and propylene carbonate PC (DEC:EMC:FEC:PC=25:45:10:20);
[0041] The linear carbonate and the cyclic carbonate are stirred and mixed evenly to obtain a first mixture; the lithium salt is added to the first mixture and stirred and mixed evenly to obtain a second mixture; the first additive and the second additive are added to the second mixture and stirred and mixed evenly to obtain an electrolyte.
[0042] 2. Preparation of positive electrode
[0043] The ternary material NCM (LiNi 0.9 Co 0.05 Mn 0.05 O 2 ) The positive electrode active material, binder PVDF (polyvinylidene fluoride), and conductive agent SP (conductive carbon black Super-P) are mixed and stirred evenly in a mass ratio of 96:1.8:2.2 to obtain a positive electrode slurry, and then the positive electrode slurry is coated on an aluminum foil through a coating process, and a positive electrode sheet is obtained after drying and cold pressing processes.
[0044] 3. Preparation of negative electrode sheet
[0045] Silicon-carbon negative electrode material, conductive agent SP (conductive carbon black Super-P), SWCNT (single-walled carbon nanotube) and binder PAA (polyacrylic acid) are mixed and stirred in a mass ratio of 83.5:8:0.5:8 to obtain negative electrode slurry, and the solid content is controlled at 30%. The negative electrode slurry is then coated on the current collector on the copper foil through a coating process, and the negative electrode sheet is obtained after vacuum drying and cold pressing processes.
[0046] 4. Selection of isolation film
[0047] Polyethylene (PE) + ceramics are selected as the isolation membrane for lithium-ion batteries.
[0048] 5. Preparation of Lithium-ion Batteries
[0049] The positive electrode sheet, the isolation film, and the negative electrode sheet are stacked in order, so that the isolation film is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then a bare battery cell is obtained; the bare battery cell is placed in an outer packaging shell, and after drying, an electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a soft-pack lithium-ion battery is obtained.
[0050] Example 2
[0051] 1. Preparation of Electrolyte
[0052] The mass proportion of the first additive in the electrolyte is 0.5%, the mass proportion of the second additive is 1.5%, the mass proportion of the linear carbonate and the cyclic carbonate in the organic solvent is 60:40, and the lithium salt concentration is 1.5 mol / L.
[0053] The first additive is 3-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-1-toluenesulfonyl-1H-pyrrolo[2,3-b]pyridine-5-carbonitrile, and the second additive has the structural formula CAS number is 2241-68-1;
[0054] The lithium salt is lithium hexafluorophosphate;
[0055] The linear carbonates are ethyl methyl carbonate EMC and methyl propyl carbonate MPC, and the cyclic carbonates are ethylene carbonate EC and propylene carbonate PC (EMC: MPC: EC: PC = 15:45:15:25);
[0056] The linear carbonate and the cyclic carbonate are stirred and mixed evenly to obtain a first mixture; the lithium salt is added to the first mixture and stirred and mixed evenly to obtain a second mixture; the first additive and the second additive are added to the second mixture and stirred and mixed evenly to obtain an electrolyte.
[0057] 2. Preparation of positive electrode
[0058] The ternary material NCM (LiNi 0.9 Co 0.05 Mn 0.05 O 2 ) The positive electrode active material, binder PVDF (polyvinylidene fluoride), and conductive agent SP (conductive carbon black Super-P) are mixed and stirred evenly in a mass ratio of 96:1.8:2.2 to obtain a positive electrode slurry, and then the positive electrode slurry is coated on an aluminum foil through a coating process, and a positive electrode sheet is obtained after drying and cold pressing processes.
[0059] 3. Preparation of negative electrode sheet
[0060] Silicon-carbon negative electrode material, conductive agent SP (conductive carbon black Super-P), SWCNT (single-walled carbon nanotube) and binder PAA (polyacrylic acid) are mixed and stirred in a mass ratio of 83.5:8:0.5:8 to obtain negative electrode slurry, and the solid content is controlled at 30%. The negative electrode slurry is then coated on the current collector on the copper foil through a coating process, and the negative electrode sheet is obtained after vacuum drying and cold pressing processes.
[0061] 4. Selection of isolation film
[0062] Polyethylene (PE) + ceramics are selected as the isolation membrane for lithium-ion batteries.
[0063] 5. Preparation of Lithium-ion Batteries
[0064] The positive electrode sheet, the isolation film, and the negative electrode sheet are stacked in order, so that the isolation film is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then a bare battery cell is obtained; the bare battery cell is placed in an outer packaging shell, and after drying, an electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a soft-pack lithium-ion battery is obtained.
[0065] Example 3
[0066] 1. Preparation of Electrolyte
[0067] The mass proportion of the first additive in the electrolyte is 2%, the mass proportion of the second additive is 0.5%, the mass proportion of the linear carbonate and the cyclic carbonate in the organic solvent is 80:20, and the lithium salt concentration is 1 mol / L.
[0068] The first additive is 3-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-1-toluenesulfonyl-1H-pyrrolo[2,3-b]pyridine-5-carbonitrile, and the second additive has the structural formula CAS number is 370-69-4;
[0069] The lithium salt is lithium hexafluorophosphate;
[0070] The linear carbonates are dimethyl carbonate DMC, diethyl carbonate DEC, and methylpropyl carbonate MPC, and the cyclic carbonate is ethylene carbonate EC (DMC:DEC:MPC:EC=25:45:10:20);
[0071] The linear carbonate and the cyclic carbonate are stirred and mixed evenly to obtain a first mixture; the lithium salt is added to the first mixture and stirred and mixed evenly to obtain a second mixture; the first additive and the second additive are added to the second mixture and stirred and mixed evenly to obtain an electrolyte.
[0072] 2. Preparation of positive electrode
[0073] The ternary material NCM (LiNi 0.9 Co 0.05 Mn 0.05 O 2 ) The positive electrode active material, binder PVDF (polyvinylidene fluoride), and conductive agent SP (conductive carbon black Super-P) are mixed and stirred evenly in a mass ratio of 96:1.8:2.2 to obtain a positive electrode slurry, and then the positive electrode slurry is coated on an aluminum foil through a coating process, and a positive electrode sheet is obtained after drying and cold pressing processes.
[0074] 3. Preparation of negative electrode sheet
[0075] Silicon-carbon negative electrode material, conductive agent SP (conductive carbon black Super-P), SWCNT (single-walled carbon nanotube) and binder PAA (polyacrylic acid) are mixed and stirred in a mass ratio of 83.5:8:0.5:8 to obtain negative electrode slurry, and the solid content is controlled at 30%. The negative electrode slurry is then coated on the current collector on the copper foil through a coating process, and the negative electrode sheet is obtained after vacuum drying and cold pressing processes.
[0076] 4. Selection of isolation film
[0077] Polyethylene (PE) + ceramics are selected as the isolation membrane for lithium-ion batteries.
[0078] 5. Preparation of Lithium-ion Batteries
[0079] The positive electrode sheet, the isolation film, and the negative electrode sheet are stacked in order, so that the isolation film is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then a bare battery cell is obtained; the bare battery cell is placed in an outer packaging shell, and after drying, an electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a soft-pack lithium-ion battery is obtained.
[0080] Example 4
[0081] The difference between this embodiment and embodiment 1 is that the electrolyte further includes a lithium salt additive (lithium bis(fluorosulfonyl)imide LiFSI), and the mass proportion of the lithium salt additive in the electrolyte is 0.3%; the remaining steps and parameter settings are consistent with embodiment 1.
[0082] Example 5
[0083] The difference between this embodiment and embodiment 1 is that the electrolyte further includes a lithium salt additive (lithium bis(trifluoromethanesulfonyl)imide LiTFSi), and the mass proportion of the lithium salt additive in the electrolyte is 3%; the remaining steps and parameter settings are consistent with embodiment 1.
[0084] Example 6
[0085] The difference between this embodiment and embodiment 1 is that the electrolyte further includes a lithium salt additive (lithium tetrafluoroborate LiBF 4 ), the mass percentage of the lithium salt additive in the electrolyte is 0.5%; the remaining steps and parameter settings are consistent with those in Example 1.
[0086] Example 7
[0087] The difference between this embodiment and embodiment 1 is that the mass proportion of the first additive in the electrolyte is 3%, and the mass proportion of the second additive in the electrolyte is 0.1%; the remaining steps and parameter settings are consistent with embodiment 1.
[0088] Example 8
[0089] The difference between this embodiment and embodiment 1 is that the mass proportion of the first additive in the electrolyte is 0.2%, and the mass proportion of the second additive in the electrolyte is 2.5%; the remaining steps and parameter settings are consistent with embodiment 1.
[0090] Example 9
[0091] The difference between this embodiment and embodiment 1 is that ethyl propionate (EP) of equal weight is used to replace the linear carbonate in embodiment 1; the remaining steps and parameter settings are consistent with those in embodiment 1.
[0092] Example 10
[0093] The difference between this embodiment and embodiment 1 is that the mass ratio of linear carbonate to cyclic carbonate is 20:80; the remaining steps and parameter settings are consistent with those in embodiment 1.
[0094] Comparative Example 1
[0095] The difference between this comparative example and Example 1 is that the electrolyte does not contain the first additive and the second additive; other steps and parameter settings are consistent with Example 1.
[0096] Comparative Example 2
[0097] The difference between this comparative example and Example 1 is that the electrolyte does not contain the first additive; the other steps and parameter settings are consistent with Example 1.
[0098] Comparative Example 3
[0099] The difference between this comparative example and Example 1 is that the electrolyte does not contain the second additive; other steps and parameter settings are consistent with Example 1.
[0100] Comparative Example 4
[0101] The difference between this comparative example and Example 1 is that the structural formula of the first additive is The CAS number is 2752449-73-1; other steps and parameter settings are consistent with those in Example 1.
[0102] Comparative Example 5
[0103] The difference between this comparative example and Example 1 is that the structural formula of the second additive is The CAS number is 66559-58-8; other steps and parameter settings are consistent with those in Example 1.
[0104] Test Method
[0105] 1. The first coulombic efficiency test of lithium battery
[0106] The lithium batteries in the above embodiments and comparative examples were subjected to the first coulombic efficiency test. The specific test steps were as follows: at 25°C, the lithium ion battery was charged to 4.2V at a constant current and constant voltage rate of 0.33C, and allowed to stand for 10 minutes. Then, the lithium ion battery was discharged to 2.5V at a constant current rate of 0.33C, and allowed to stand for 10 minutes. The first coulombic efficiency of the lithium ion battery was calculated.
[0107] First coulombic efficiency (%) = total capacity of the lithium-ion battery discharged at 0.33C for the first time / total capacity of the lithium-ion battery charged at 0.33C for the first time × 100%.
[0108] 2. Lithium battery cycle performance test
[0109] 2.1. Lithium battery capacity retention rate during normal temperature cycling
[0110] The lithium batteries in the above embodiments and comparative examples were tested for capacity retention rate under normal temperature cycles. The specific test steps were as follows: at 25°C, the lithium ion battery was charged to 4.2V at a constant current and constant voltage rate of 1C, with a cut-off current of 0.05C, and allowed to stand for 10 minutes. Then, the lithium ion battery was discharged to 2.5V at a constant current rate of 1C, and allowed to stand for 10 minutes. This was considered one charge and discharge cycle. The lithium ion battery was charged and discharged for 1000 cycles according to the above method, and the capacity retention rate of the lithium ion battery after 1000 cycles of charge and discharge at 1C / 1C was calculated.
[0111] 2.2. Lithium battery high temperature cycle capacity retention rate
[0112] The lithium batteries in the above embodiments and comparative examples were tested for capacity retention rate under normal temperature cycles. The specific test steps were as follows: at 45°C, the lithium ion battery was charged to 4.2V at a constant current and constant voltage rate of 1C, with a cut-off current of 0.05C, and allowed to stand for 10 minutes. Then, the lithium ion battery was discharged to 2.5V at a constant current rate of 1C, and allowed to stand for 10 minutes. This was considered one charge and discharge cycle. The lithium ion battery was charged and discharged for 1000 cycles according to the above method, and the capacity retention rate of the lithium ion battery after 1000 cycles of charge and discharge at 1C / 1C was calculated.
[0113] The capacity retention rate (%) of a lithium-ion battery after N cycles = (discharge capacity at the Nth cycle / initial discharge capacity) × 100%, where N is the number of cycles of the lithium-ion battery.
[0114] 3. Rate performance test
[0115] The lithium batteries of the above embodiments and comparative examples were subjected to rate performance tests, and the specific test steps were as follows: at 25°C, the lithium ion battery was discharged at a constant current rate of 1C to 2.5V, and allowed to stand for 10 minutes, and then the lithium ion battery was charged at a constant current and constant voltage rate of 6C to 4.2V, with a cut-off current of 0.05C, and allowed to stand for 10 minutes, and the constant current charging capacity Q1 and the constant current and constant voltage charging total capacity Q2 of the lithium ion battery were recorded, and the 6C rate charging constant current charging ratio was calculated according to the following formula: 6C rate charging constant current charging ratio = constant current charging capacity Q1 / constant current and constant voltage charging total capacity Q2 × 100%.
[0116] 4. Safety performance test
[0117] The lithium batteries of the above embodiments and comparative examples are subjected to thermal runaway tests, and the specific test steps are as follows: the test sample is heated from room temperature to 45±2°C in the chamber, and after being left for 90 minutes, the change in the temperature rise rate of the battery is detected. If the temperature rise exceeds 0.2°C within 10 minutes (i.e., SHR>0.02°C / min), it is considered that a self-exothermic reaction occurs inside the battery, and an adiabatic environment is maintained until the battery undergoes thermal runaway; if the temperature rise does not exceed 0.2°C within 10 minutes (i.e., SHR≤0.02°C / min), continue to the next step temperature rise test; each temperature step is 5°C, and the steps are repeated on each step. The ARC test temperature range is 45-300°C, the starting temperature of self-heat generation is T1 (temperature rise rate SHR>0.02°C / min), and the starting temperature of thermal runaway is T2 (temperature rise rate SHR>1°C / min).
[0118] Table 1
[0119]
[0120] In combination with Examples 1-3, Comparative Examples 1-5 and Table 1, it can be seen that in the present application, by using the first additive and the second additive in combination, not only can the stability of the electrolyte be improved to improve the stability of the negative electrode interface film, but also a protective layer containing alkyl phosphorus can be formed on the surface of the positive electrode to effectively inhibit the dissolution of transition metal ions at the positive electrode, avoid the negative impact of transition metal ions on the film formation stability of the negative electrode SEI film, and help to improve the cycle capacity retention rate and thermal stability of the lithium battery; and, the combination of the sulfonyl group, pyridine group and fluorine element in the two additives can not only improve the flame retardancy of the electrolyte, but also help to improve the ionic conductivity of the electrolyte, thereby further improving the self-heating starting temperature and rate performance of the lithium battery.
[0121] Combining Example 1, Examples 4-6 and Table 1, it can be seen that by adding a suitable lithium salt additive to the electrolyte, the ionic conductivity of the electrolyte can be improved, which helps to improve the cycle capacity retention rate of the lithium battery.
[0122] In combination with Example 1, Examples 7-8 and Table 1, it can be seen that when the usage ratio of the first additive to the second additive is too high or too low, it is not conducive to improving the stability of the positive electrode interface film and the negative electrode interface film, and will reduce the coordination effect of the sulfonyl group, pyridine group and fluorine element in the additive, which is not conducive to improving the flame retardant properties of the electrolyte and the cycle performance of the lithium battery. Therefore, the cycle performance and self-heating starting temperature of the lithium battery of Examples 7-8 are lower than those of the lithium battery of Example 1.
[0123] In combination with Example 1, Examples 9-10 and Table 1, it can be seen that the present application selects cyclic carbonates and linear carbonates as organic solvents and controls the mass ratio of cyclic carbonates to linear carbonates, which not only helps to improve the stability of the electrolyte and provide a stable environmental basis for the combination of the first additive and the second additive, but also can promote uniform film formation on the surface of the negative electrode active material. Therefore, the cycle performance and first-effect performance of the lithium batteries of Examples 9-10 are lower than those of the lithium battery of Example 1.
[0124] The above embodiments are only used to illustrate the technical solution of the present application rather than to limit the protection scope of the present application. Although the present application is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solution of the present application can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present application.
Claims
1. A multifunctional electrolyte, characterized in that: The invention comprises a first additive and a second additive, wherein the first additive comprises 3-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-1-toluenesulfonyl-1H-pyrrolo[2,3-b]pyridine-5-carbonitrile; and the chemical structure of the second additive is as shown in Formula I: Wherein, R1, R2, and R3 are each independently selected from any one of -CH2CF3, -CHCF3CF3, and -CH2CF2CHF2.
2. The multifunctional electrolyte according to claim 1, characterized in that: The mass proportion of the first additive in the electrolyte is 0.5%-2%.
3. The multifunctional electrolyte according to claim 1, characterized in that: The mass proportion of the second additive in the electrolyte is 0.5%-1.5%.
4. The multifunctional electrolyte according to any one of claims 1 to 3, characterized in that: It also includes organic solvents, lithium salts and lithium salt additives.
5. The multifunctional electrolyte according to claim 4, characterized in that: The lithium salt additive includes at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide and lithium tetrafluoroborate.
6. The multifunctional electrolyte according to claim 4, characterized in that: The lithium salt additive accounts for 0.2%-3% by mass in the electrolyte.
7. The multifunctional electrolyte according to claim 4, characterized in that: The organic solvent includes at least one of a linear carbonate and a cyclic carbonate.
8. The multifunctional electrolyte according to claim 7, characterized in that: The linear carbonate includes at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and methyl propyl carbonate; the cyclic carbonate includes at least one of ethylene carbonate, fluoroethylene carbonate and propylene carbonate.
9. The multifunctional electrolyte according to claim 7, characterized in that: The mass ratio of the linear carbonate to the cyclic carbonate is 60-80:20-40.
10. A lithium ion battery, characterized in that: The invention comprises a positive electrode sheet, a separator, a negative electrode sheet and a multifunctional electrolyte as claimed in any one of claims 1 to 9.
Citation Information
Patent Citations
Difunctional electrolyte additive and lithium ion battery electrolyte containing same
CN110931862A
Multifunctional high-voltage electrolyte and application thereof in lithium ion battery
CN113782830A
Electrolyte and battery comprising same
CN115332626A
Compounds for enhancing the solid-electrolyte interphase (SEI) of silicon-based anode materials in lithium-ion batteries, and electrolytes, batteries, and methods relating thereto
US20240204253A1
Small molecule inhibitors of NF-KB inducing kinase
WO2022104348A1